2006
DOI: 10.1080/15295192.2006.9681304
|View full text |Cite
|
Sign up to set email alerts
|

Fathering in Infancy: Mutuality and Stability Between 8 and 16 Months

Abstract: SYNOPSISObjective. This longitudinal investigation explores how fathers engage with their infants, how their behaviors matter within and across developmental time, and how demographic and social factors affect the quality of the fatherinfant relationship. Design. Participants were 74 racially and ethnically diverse, low-income fathers from the Father and Newborn Study (FANS) and their 8-and 16-month-old infants (36 boys, 38 girls). Father -infant interactions were videotaped during semistructured free play in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 32 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Somewhat counter to stereotypes about low-income, urban fathers of color, fathers' high levels of involvement at birth were much more likely to maintain over time than to present a pattern of Shannon et al 2006), but advances that work by exploring pathways in a majority immigrant sample. What might explain associations between fathers' prenatal involvement and later involvement?…”
Section: Similarities and Differences In Patterns Over Timementioning
confidence: 78%
See 1 more Smart Citation
“…Somewhat counter to stereotypes about low-income, urban fathers of color, fathers' high levels of involvement at birth were much more likely to maintain over time than to present a pattern of Shannon et al 2006), but advances that work by exploring pathways in a majority immigrant sample. What might explain associations between fathers' prenatal involvement and later involvement?…”
Section: Similarities and Differences In Patterns Over Timementioning
confidence: 78%
“…Recent analysis of the ECLS-B (described above; BronteTinkew et al 2007) found that fathers' prenatal behaviors predicted fathers' warmth and engagement in cognitively stimulating activities with their 9 month olds. In the Early Head Start National Evaluation Project, measures of fathers' prenatal involvement (e.g., accompanying mother to prenatal visits, being present at the newborn's birth) predicted fathers' presence in their children's lives up to 5 years later (Shannon et al 2006). Over 90% of fathers, who displayed high levels of prenatal involvement, still saw their children at least three times per week during the prekindergarten period.…”
Section: Prenatal Involvement and Later Father Involvementmentioning
confidence: 99%
“…All instruments reviewed in this paper have also Attachment & Human Development 497 been used with fathers and have shown meaningful associations between paternal sensitivity and a variety of other variables (e.g., Kelley et al, 1998;Lewis & Lamb, 2003;Lucassen et al, 2011;Shannon, Tamis-LeMonda, & Cabrera, 2006;Shannon, Tamis-LeMonda, London, & Cabrera, 2002). However, it has been suggested that other aspects of fatherchild interactions may be more salient for child development, such as challenging and stimulating play (Grossmann, Grossmann, Kindler, & Zimmermann, 2008).…”
Section: Attachment and Human Development 495mentioning
confidence: 94%
“…This is an important juncture at which to examine gatekeeping because this transition has been described as a “critical period” (Doherty, Erickson, & LaRossa, 2006, p. 438) for the establishment of father-child relationships. Given that early levels of father involvement in infancy tend to persist (Shannon, Tamis-LeMonda, & Cabrera, 2006), maternal gatekeeping in the early postpartum months could have a particularly long-lasting effect on father involvement. We followed 182 dual-earner expectant couples from the third trimester through 3 months postpartum.…”
Section: Introductionmentioning
confidence: 99%